Fiscal convergence in the West African Monetary Zone - Olorunsola E. Olowofeso; Maimuna John-Sowe; Santigie M. Kargbo; Sani Bawa; Isatou Mendy; Kormay Adams; Adegoke Ibrahim Adeleke; Yaya Cham (West African Monetary Institute (WAMI), 2021)
Achieving fiscal convergence between countries of a monetary union helps in the design and implementation of policies to strengthen macroeconomic convergence, which mitigates the contagion effects of macroeconomic instability and ensures the long-term viability of the proposed union. This paper assesses the extent of fiscal convergence among the West African Monetary Zone (WAMZ) countries and explores the response of fiscal convergence to divergence of public debt levels, inflation rates and current account balances to determine whether strengthening of policy synchronisation would contribute to fostering fiscal convergence in these countries. Allowing for heterogeneous fiscal policies among the WAMZ countries, the result from the log t convergence test estimated over the period 2001-2019 provides strong evidence of fiscal divergence among these countries during the period. Equally, by exploiting nonlinearities in policy behaviour among the WAMZ countries in the response of fiscal convergence to policy synchronisation, the results from the dynamic panel threshold models show remarkably strong evidence that reducing divergence in public debt levels, inflation rates and current account balances would reduce fiscal divergence. Given these empirical insights, WAMZ countries would need to strengthen fiscal consolidation measures to improve the primary balance and enhance capacity to reduce public debt to sustainable levels. Similarly, these countries should provide support to enhance domestic productive capacity and diversify the export sector to improve external sector performance. These measures should be accompanied by additional fiscal reforms to constrain discretion in fiscal policies to promote fiscal convergence, including the implementation of fiscal rules and Fiscal Responsibility Act.
Keywords: C33; E62; H60; O55; 330; fiscal convergence; public debt; inflation; current account; dynamic panel; WAMZ